New record of Velvety Black Tyrant Knipolegus nigerrimus (Vieillot, 1818) (Passeriformes, Tyrannidae) at low altitude, in a Caatinga area, Paraíba, Brazil - Ricardo Henrique Pereira da Silva; José Alan Sales Souza; Bruno Pinho de Lucena; Erich de Freitas Mariano (Acta Biológica Catarinense, 2024)
Knipolegus nigerrimus is a widely distributed bird species in the Caatinga and has been recorded at altitudes between 560 and 1000 m. Here, we describe the occurrence of K. nigerrimus at an altitude lower than that recorded in the literature. A male individual was recorded during an avifauna study conducted in 2022 in the municipality of Passagem, Paraíba, Brazil. The individual was observed making short flights near a rocky wall and landing on rocks in the vicinity. At that time, the individual was photographed and photographs were used to identify the species. One possible explanation for what happened is that it moved to a low-altitude environment in search of a watercourse present at the site. However, the observed behaviour is described in the literature as parental care behaviour, which may indicate the presence of a nest at the site. This record is important because it shows a possible behavioural adaptation.